DESAIN DASAR MESIN INJECTION MOLDING UNTUK PROSES CASTING SAMPEL PROPELAN PADAT MENGGUNAKAN SOFTWARE SOLIDWORKS - Febriyanto, Ady; Supardi, Nurul Iman; Yulia Azatil Ismah (UNIB Press, 2025)
The injection molding machine for the solid propellant sample casting process is a tool for making a sample in the form of a solid propellant sample plate, this tool is designed to make work easier when carrying out the process of making solid propellant samples. The needs of the propellant industry in Indonesia are very large and important considering the need to develop solid propellant samples and munitions for the national arsenal, namely to promote and facilitate the exchange of technical information and programs. itself consists of two molds with sizes, namely 25cm diameter, 10cm high and 17cm diameter, 5cm high, frame, cember, hydraulic. The most important component in solid propellant sample injection molding is the solid propellant sample mold. Therefore, it must be strong and sturdy to hold the solid propellant sample so that it does not come out during printing with hydraulic pressure.The manufacture of solid propellant injection molding was assisted with Solidwork Software in this research.Keyword: Rocket, Propellant, injection molding.